Seroprevalence of Hepatitis B virus Infection by Quantitative Chemiluminescent in Tabriz (North West of Iran), 2010-2011 - Hajizadeh, Nader; Farhadi, Samad; Hamidi, Masoud; Ashrafi-Hafez, Asghar; Ahmadi, Nayeb Ali (Novelty in Biomedicine, 2014)
Background: Hepatitis B is considered as one of the most common infectious diseases. The contamination of this virus has caused hygienic problems all over the world. Liver cirrhosis and hepatocellular carcinoma are most important consequences of this disease. The purpose of this study is to determine the rate of infection in Tabriz North West of Iran. Materials and Methods: This study is carried out, on partial and short time basis between 2010 and 2011, on test results of 21421 examined individuals whom have visited clinics in Tabriz. HBsAg of the samples was analyzed with chemiluminescence apparatus and finally, SPSS software was used to conduct the statistical examination of the results. Results: Among 21421 examined individuals (5021 cases in 2010 and 16400 cases in 2011), 594 samples (2.77%) were reported positive and 20827 samples (97.23%) were reported negative. Conclusion: According to the results, gender was not a determining factor affecting the susceptibility of patients. Our country is endemic to this disease, so diagnostic and preventive methods are crucial, more over comprehensive national vaccination can help to noticeably reduce the infectious cases caused by the disease.